Prosedur Penerjemahan Istilah Ekonomi dalam Teks Online Bloomberg: Kajian Penerjemahan Beranotasi - Sinaga, Suisan; Jayantini, I Gusti Agung Sri Rwa (Center of Language and Cultural Studies, 2023)
Translating economic texts is a challenge for translators because they have to understand global economic dynamics and specific terms that are frequently not understood. This study discusses the procedures applied to translate economic terms in an economic text describing Indonesian capital market. The analyzed data were English economic terms from the online media Bloomberg,